Development of an aqueous ultrasound‐assisted extraction process of bioactive compounds from beet leaves: A proposal for reducing losses and increasing biomass utilisation - Nutter, Julia (2020)
BACKGROUND: Red beet plants are cultivated worldwide for the consumption of their roots, generating large amounts of unexploited by-products. In particular, beet leaves (BLs) represent about 50% of the whole plant and are usually discarded as waste. This constitutes not only an economic issue, since multiple resources invested in the production will be wasted, but also an environmental problem because of the pollution associated with their disposal. However, BLs comprise an important source of functional compounds (polyphenols and betalains) that could be recovered from the raw material, representing a sustainable solution for the underutilization of this by-product. This study proposes the recovery of polyphenols and betalains using an aqueous ultrasound-assisted extraction (UAE) process at different powers (35, 50, and 100 W) that was characterized and optimized. RESULTS: UAE significantly enhanced the recovery of bioactive compounds and shortened the time required for extraction in comparison with traditional macerations (35 < 50 < 100 W). During UAE, the temperature of the systems increased as a function of the power applied, favouring the recovery of these phytochemicals. Additionally, a Box–Behnken design and response surface methodology were employed to optimize UAE conditions (90 W ultrasound power, 1:20 solid:liquid ratio, 16 min extraction time), under which the yields were 14.9 mg g−1 (polyphenols), 949.1 μg g−1 (betaxanthins), and 562.2 μg g−1 (betacyanins), consistent with the values predicted by the models. CONCLUSION: This study enabled the development of a green-solvent UAE process that constitutes an effective post-harvest by-products strategy to minimize losses and increase biomass utilization through the recovery of bioactive compounds from BLs, promoting sustainability in the agri-food chain.